2016
DOI: 10.1002/app.43636
|View full text |Cite
|
Sign up to set email alerts
|

Antisolvent crystallization and solid‐state polymerization of bisphenol‐A polycarbonate

Abstract: Bisphenol‐A polycarbonate (BAPC) was synthesized by solid‐state polymerization (SSP) using a semicrystalline prepolymer crystallized by antisolvent method. The antisolvent crystallization was investigated as a function of antisolvent types using X‐ray diffraction (XRD), different scanning calorimetry (DSC), and scanning electron microscopes (SEM). The results showed antisolvent types had a significant effect on the crystallization of BAPC. Prepolymer induced by acetone as an antisolvent gained a higher crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…17 Xuesong Chang et al synthesized a high-molecular weight BPA polycarbonate through SSP using prepolymer crystallized by antisolvent method. 20 They investigated the antisolvent types to find a significant effect on the crystallization of BPA polycarbonate. Stephen M. Gross et al also took advantage of supercritical CO 2 to synthesize BPA polycarbonate by SSP, inducing crystallinity in low-molecular-weight polycarbonate beads.…”
Section: Introductionmentioning
confidence: 99%
“…17 Xuesong Chang et al synthesized a high-molecular weight BPA polycarbonate through SSP using prepolymer crystallized by antisolvent method. 20 They investigated the antisolvent types to find a significant effect on the crystallization of BPA polycarbonate. Stephen M. Gross et al also took advantage of supercritical CO 2 to synthesize BPA polycarbonate by SSP, inducing crystallinity in low-molecular-weight polycarbonate beads.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of plasticizers can enhance the movement of molecular chains and thus promote the crystal growth. For instance, common PC plasticizers include organic solvents such as acetone [20][21][22], carbon tetrachloride [23,24], tetrahydrofuran [24,25], ethyl acetate [26], chloroform [27], and supercritical CO 2 (SCCO 2 ) [28,29] can enhance the free volume and movement of PC molecular chains, and promote the ordering of molecular chanis into regular helica segments, which serve as crystal nuclie to initiate PC crystalization. Similarlly, flexible polymers such as polycaprolactone [30,31], polyethylene glycol [32], epoxy resins [33], esters such as diallyl phthalate [34], tributyl citrate [35,36], and small molecule liquid crystals such as cholesterol nonanoate (CN) [37,38] enhance the flexibility of PC to alevate the crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that some crystalline monomers can be polymerized in the solid state and a high conversion rate is achieved. [6][7][8] Compared with liquid-phase polymerization, solid-state photopolymerization still has the advantages of short induction time, small volume shrinkage, and high product purity due to the absence of solvent and even initiator. Solid-state polymerization can be conducted in a variety of ways, among which photo-initiated solid-state polymerization has been widely studied for its low temperature and eco-friendly properties.…”
Section: Introductionmentioning
confidence: 99%